Declining social mobility? Evidence from five linked censuses in England and Wales 1971–2011. (18th September 2017) - Buscha, Franz; Sturgis, Patrick
Abstract: In this paper we add to the existing evidence base on recent trends in inter‐generational social mobility in England and Wales. We analyse data from the Office for National Statistics Longitudinal Study (ONS‐LS), which links individual records from the five decennial censuses between 1971 and 2011. The ONS‐LS is an excellent data resource for the study of social mobility because it has a very large sample size, excellent population coverage and low rates of nonresponse and attrition across waves. Additionally, the structure of the study means that we can observe the occupations of LS‐members' parents when they were children and follow their own progress in the labour market at regular intervals into middle age. Counter to widespread prevailing beliefs, our results show evidence of a small but significant increase in social fluidity between 1950s and the 1980s for both men and women.